Comparative study between a direct DNA quantification methodology and the standardized methodology in the forensic workflow. (December 2017) - Dinis, V.; Bento, A.M.; Teixeira, A.L.; Gouveia, N.; Bogas, V.; Porto, M.J.; Corte-Real, F.
Abstract: Being the forensic workflow a long process, with many steps associated, it is highly desirable the development of a method that will allow to select more quickly samples with enough DNA quantity to proceed to amplification. A comparative study was performed to evaluate the viability of a direct DNA quantification methodology in the forensic workflow.